IMPACT OF VITAMIN D STATUS, IRON PROFILES, AND TRACE ELEMENTS IMBALANCES ON CARDIOMETABOLIC RISK FACTORS IN WOMEN WITH SUBCLINICAL HYPOTHYROIDISM - Sulaiman, Chiman H; Mohammed, Lina Y; Hami, Mohammed A (Science Journal of University of Zakho, 2025)
The main aim of this study was to elucidate the impact of vitamin D, iron profile, and trace elements imbalances on cardiometabolic risk factors in newly diagnosed women with subclinical hypothyroid. Fifty newly diagnosed subclinical hypothyroid (SCHT) females, aged 18-50 years, and 40 healthy females matched in age with patients were enrolled in the present study. Thyroid-stimulating hormone (TSH), Free thyroxin (FT4), Free triiodothyronine (FT3), vitamin D, and serum ferritin were measured using an electrochemiluminescence assay. Lipid profile, serum iron (Fe), and unsaturated iron binding capacity (UIBC) were analyzed by a photometric measuring unit. Serum zinc (Zn), magnesium (Mg), and copper (Cu) were quantified using a colorimetric method. The current study indicated a significant increase in cardiometabolic risk factors such as fasting blood sugar (FBS), lipid profile, Triglyceride-glucose index (TyGi), and Atherogenic index of plasma (AIP) in SCHT, in contrast to the healthy group. Furthermore, a strong association was noted between elevated TSH and lipid profile, fasting blood sugar, AIP, and TyGi. Additionally, a substantial association was indicated between reduced vitamin D, ferritin, magnesium levels, and elevated copper levels with cardiometabolic risk factors. The current study concluded that low vitamin D, ferritin, magnesium levels, and elevated copper levels are linked with cardiometabolic risk factors in females diagnosed with subclinical hypothyroidism. Reduced vitamin D, magnesium levels, disrupted iron metabolism, and elevated serum copper were linked to heightened atherogenic risk and metabolic abnormalities
Keywords: cardiometabolic risk factors; subclinical hypothyroidism; vitamin D; iron profile; trace elements